Collision-based Electrochemistry for Investigation of Direct Electron Transfer of a Single Enzyme Molecule. (2017) - Sekretaryova, Alina N.; Vagin, Mikhail Yu.; Turner, Anthony P.F.; Eriksson, Mats
Abstract: Electron transfer between a biorecognition element and an electrode is an essential element of bioelectrocatalytic systems, such as biosensors and biofuel cells. The number of working systems based on direct electron communication is limited and detailed investigations of the mechanism of the process are still required. Here, we present the use of a novel approach of collision-based bioelectrocatalysis to monitor electrocatalytic currents from individual redox enzyme molecules. This approach allowed us to calculate the individual turnover rates of these molecules and investigate the influence of the applied potential, pH and additions of inhibitor on the observed rates of direct electron transfer.